2008
DOI: 10.1086/589228
|View full text |Cite
|
Sign up to set email alerts
|

IC 4406: A Radio‐Infrared View

Abstract: IC 4406 is a large (about 100 00 ; 30 00 ) southern bipolar planetary nebula composed of two elongated lobes extending from a bright central region where there is evidence for the presence of a large torus of gas and dust. We show new observations of this source performed with IRAC (Spitzer Space Telescope) and the Australia Telescope Compact Array. The radio maps show that the flux from the ionized gas is concentrated in the bright central region and originates in a clumpy structure previously observed in H, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Nevertheless, in the near-IR, where the central star and dust fluxes are at a minimum, the free-free contribution to the observed flux may not be much smaller than the contributions from the other emitting components. For example, in the evolved PN IC 4406 a near-IR excess, previously supposed to indicate a hot-dust component, has been explained as a free-free contribution (Cerrigone et al 2008b). Therefore, we decided to estimate the Gaunt factor following Karzas & Latter (1961) for a 10 4 K electron temperature, extending the calculation of the emission curve from the cm range to 0.8 µm.…”
Section: Modeling the Spectral Energy Distributionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, in the near-IR, where the central star and dust fluxes are at a minimum, the free-free contribution to the observed flux may not be much smaller than the contributions from the other emitting components. For example, in the evolved PN IC 4406 a near-IR excess, previously supposed to indicate a hot-dust component, has been explained as a free-free contribution (Cerrigone et al 2008b). Therefore, we decided to estimate the Gaunt factor following Karzas & Latter (1961) for a 10 4 K electron temperature, extending the calculation of the emission curve from the cm range to 0.8 µm.…”
Section: Modeling the Spectral Energy Distributionmentioning
confidence: 99%
“…Y is the value given as input in DUSTY and τ 100 is given by the code as an output. For δ, whose value depends on the evolutionary stage, we consider a typical value of 200. k 100 depends on the chemistry of the envelope: we use 92 g cm −2 for amorphous carbon (Cerrigone et al 2008b) and 34 g cm −2 for silicates (Sarkar & Sahai 2006). We have used the values for silicates not only in the targets that we have classified as O-rich, but also in mixed-chemistry environments, neglecting any contribution from C-bearing molecules.…”
Section: Circumstellar Mass Calculationmentioning
confidence: 99%
“…Phillips & Ramos-Larios (2010) extended their analysis to seven bipolar PNe, assessing the roles of PAH emission from PDRs and shock excited H 2 emission, and discussing the color variations from the cores to the lobes. Cerrigone et al (2008) analyzed IRAC images, in conjunction with 4.8 and 8.6 GHz radio continuum observations, of the bipolar PN IC 4406, and concluded that there exist at least three dust components at temperatures ranging from 57 to 700 K.…”
Section: Irac Observations Of Pnementioning
confidence: 99%